The Sebata Group : doing business the African way - Gaylard, Alison; Ndaba, Zanele ([London] : SAGE, 2016)
Matome Modipa, executive chairman and founder of the Sebata Group of technical engineering and management consultants, enjoyed coming to work. His offices in Midrand, near Johannesburg, had an open and friendly feel, and the pervading ethos reflected the African philosophies of ubuntu and letsema that he had worked hard to instil in the organisation. Sebata had enjoyed steady growth since its inception in 2006. Now, in October 2013, the company was on the cusp of further expansion, and Modipa wondered how he was going to keep these philosophies alive at Sebata.
Originally Published in: Gaylard, A., & Ndaba, Z. (2014). The Sebata Group: Doing Business the African Way. WBS-2014-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Corporations -- Growth -- Case studies